Rural‐Urban Differences in Access to Preventive Health Care Among Publicly Insured Minnesotans. (14th March 2017) - Loftus, John; Allen, Elizabeth M.; Call, Kathleen Thiede; Everson‐Rose, Susan A.
Abstract: Purpose: Reduced access to care and barriers have been shown in rural populations and in publicly insured populations. Barriers limiting health care access in publicly insured populations living in rural areas are not understood. This study investigates rural‐urban differences in system‐, provider‐, and individual‐level barriers and access to preventive care among adults and children enrolled in a public insurance program in Minnesota. Methods: This was a secondary analysis of a 2008 statewide, cross‐sectional survey of publicly insured adults and children (n = 4, 388) investigating barriers associated with low utilization of preventive care. Sampling was stratified with oversampling of racial/ethnic minorities. Results: Rural enrollees were more likely to report no past year preventive care compared to urban enrollees. However, this difference was no longer statistically significant after controlling for demographic and socioeconomic factors (OR: 1.37, 95% CI: 1.00‐1.88). Provider‐ and system‐level barriers associated with low use of preventive care among rural enrollees included discrimination based on public insurance status (OR: 2.26, 95% CI: 1.34‐2.38), cost of care concerns (OR: 1.72, 95% CI: 1.03‐2.89) and uncertainty about care being covered by insurance (OR: 1.70, 95% CI: 1.01‐2.85). These and additional provider‐level barriers were also identified among urban enrollees. Conclusions: Discrimination, cost of care, and uncertainty about insurance coverage inhibit access in both the rural and urban samples. These barriers are worthy targets of interventions for publicly insured populations regardless of residence. Future studies should investigate additional factors associated with access disparities based on rural‐urban residence.